PANDUAN UNGGAH MANDIRI KARYA ILMIAH : Untuk Mahasiswa Universitas Pembangunan Nasional Veteran Jakarta - Nacita Putri Anzelia (2021)
The economy of a country can be seen from the economic growth through the public and monetary. This paper will discuss how the effect of the exchange rate, the money supply and the inflation rate in Indonesia. This study will discuss that the three monetary factors will affect Indonesia's economic growth as seen from the Gross Domestic Product (GDP). The data used in this research is secondary data in the form of time series data for the period 1989-2019. This study uses multiple regression analysis tools with the Ordinary Least Square (OLS) method and uses the Classical Assumption Test. The research results prove that the exchange rate and the money supply have a significant positive effect on economic growth. Inflation has a significant negative effect on economic growth. It is hoped that this research can be used as a material consideration for the government and Bank Indonesia to determine a better monetary policy related to the development of economic growth in Indonesia.